Le « Jardin d’Amour » de Yinka Shonibare au musée du quai Branly ou : quand l'« autre » s'y met - Bernard Müller (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The author of this contribution attempts to expose what implies, both on a curatorial and a theoretical level, a contemporary art exhibition in a museum of mankind: “Jardin d’amour” by Yinka Shonibare at the musée du quai Branly in Paris (April to July 2007). In this outlook he develops an epistemological reflection on the “Other".